2018
DOI: 10.1016/j.polymertesting.2017.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Nanocomposites with shape memory behavior based on a segmented polyurethane and magnetic nanostructures

Abstract: Shape-memory composites based on a commercial segmented polyurethane and magnetite (Fe 3 O 4) nanoparticles (NPs) were prepared by a simple suspension casting method. The properties of the resulting nanocomposites, containing 1 to 10 nominal wt.% magnetic particles, were evaluated by thermogravimetric tests, contact angle measurements, differential scanning calorimetry, infrared and X-ray spectroscopy, static and thermal cyclic tensile tests, dynamic mechanical analysis and experiments of alternating-magnetic-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 47 publications
5
20
0
Order By: Relevance
“…This effect was also noticed in other related works, for example, in our previous work we associated it with the changes in the conformation of the chitosan surrounding the particles in comparison with the chitosan in bulk [Kloster et al, 2015]. Soto et al (2018) also reported a decreased thermal stability, in comparison with that of the neat polymeric matrix, in their nanocomposite films based on a commercial shape memory polyurethane and different contents of magnetic iron oxides, which was associated to the increase in the thermal conductivity and thermal diffusivity of the material due to the addition of MNP. Additionally, Bertolino et al (2018) found that their nanocomposites based on chitosan and halloysite nanotubes, also prepared by casting, did not present any thermal stabilization effect due to the presence of particles.…”
supporting
confidence: 82%
See 1 more Smart Citation
“…This effect was also noticed in other related works, for example, in our previous work we associated it with the changes in the conformation of the chitosan surrounding the particles in comparison with the chitosan in bulk [Kloster et al, 2015]. Soto et al (2018) also reported a decreased thermal stability, in comparison with that of the neat polymeric matrix, in their nanocomposite films based on a commercial shape memory polyurethane and different contents of magnetic iron oxides, which was associated to the increase in the thermal conductivity and thermal diffusivity of the material due to the addition of MNP. Additionally, Bertolino et al (2018) found that their nanocomposites based on chitosan and halloysite nanotubes, also prepared by casting, did not present any thermal stabilization effect due to the presence of particles.…”
supporting
confidence: 82%
“…et al (2018)[45] also reported a decreased thermal stability, in comparison with that of the neat polymeric matrix, in their nanocomposite films based on a commercial shape memory polyurethane and different contents of magnetic iron oxides, which was associated to the increase in the thermal conductivity and thermal diffusivity of the material due to the addition of MNP.Additionally, Bertolino et al (2018)[46] found that their nanocomposites based on chitosan and halloysite nanotubes, also prepared by casting, did not present any thermal stabilization effect due to the presence of particles. They related this fact to the adsorption of positive biopolymer on the halloysite external surface, also with positive charge.…”
mentioning
confidence: 97%
“…However, all the samples were able to fix almost 100% of the deformed shape at 60°C. The shape memory results indicate that the incorporation of GQD nanoparticles in PU matrix has improved both SF and recovery ratios, which could not be achieved in some previous studies 8,9,36 …”
Section: Resultsmentioning
confidence: 70%
“…The highest SF and recovery ratios (more than 95%) were obtained by incorporating of hybrid GO:rGO in TPU matrix. Soto el al 8 prepared magneto‐responsive SMPU nanocomposites via solution casting method. Their studies revealed that the presence of magnetic nanoparticles have not significantly altered the crystallinity, transition temperature, and morphology of the resulting nanocomposites.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years shape memory polymers (SMPs) have found growing interests because of their special and unique applications in medical, electronics, hightech industries as well as daily life [1,2]. SMPs are found to be a superior choice for developing novel intelligent polymers due to their low density, economic cost, processability, appreciable shape recovery properties [1,2], high repeated deformation and possibility to modify the material by introducing fillers [3,4]; moreover, their properties can be fine-tuned to requirements via changes in materials additives and synthesis methods [3]. These smart polymers can be programmed so as to change their original permanent shape into a secondary temporary shape through exposing them to external stimuli such as temperature, light, chemicals, pH, magnetic field, etc.…”
Section: Introductionmentioning
confidence: 99%